Reannotation of Mycoplasma hyopneumoniae hypothetical proteins revealed novel potential virulence factors. (January 2022) - Tavares, Bryan Augusto da Rosa; Paes, Jéssica Andrade; Zaha, Arnaldo; Ferreira, Henrique Bunselmeyer
Abstract: Mycoplasma hyopneumoniae is a bacterium that inhabits the swine respiratory tract, causing porcine enzootic pneumonia, which generates significant economic losses to the swine industry worldwide. The knowledge on M. hyopneumoniae biology and virulence have been significantly increased by genomics studies. However, around 30% of the predicted proteins remained of unknown function so far. According to the original annotation, the genome of M. hyopneumoniae 7448, a Brazilian pathogenic strain, had 693 coding DNA sequences, 244 of which were annotated as coding for hypothetical or uncharacterized proteins. Among them, there may be still several genes coding for unknown virulence factors. Therefore, this study aimed to functionally reannotate the whole set of 244 M. hyopneumoniae 7448 proteins of unknown function based on currently available database and bioinformatic tools, in order to predict novel potential virulence factors. Predictions of physicochemical properties, subcellular localization, function, overall association to virulence and antigenicity are provided. With that, 159 out of the set of 244 proteins of unknown function had a putative function associated to them, allowing identification of novel enzymes, membrane transporters, lipoproteins, DNA-binding proteins and adhesins. Furthermore, 139 proteins were generally associated to virulence, 14 of which had a function assigned and were differentially expressed between pathogenic and non-pathogenic strains of M. hyopneumoniae. Moreover, all extracellular or cytoplasmic membrane predicted proteins had putative epitopes identified. Overall, these analyses improved the functional annotation of M. hyopneumoniae 7448 genome from 65% to 87% and allowed the identification of new potential virulence factors. Highlights: Annotation of M. hyopneumoniae 7448 genome presents a large fraction of genes annotated as coding for hypothetical proteins. Reannotation of M. hyopneumoniae 7448 genome improved the original annotation from 65% to 87%. Most of proteins of unknown function were predicted as localized at cell surface and/or extracellular fraction. 159 proteins of unknown function had a putative function associated to them. Several potential virulence factors were predicted among the proteins with putative functions predicted.